A Review of Perovskite-based Lithium-Ion Battery Materials - Beladona, Siti Unvaresi Misonia; Purwanto, Ferry; Jumiati, Jumiati; Simanjuntak, Elfrida Roulina; Simarmata, Sari Namarito; Pasaribu, Marvin Horale; Sylvani, Miranti Maya; Putra, Riandy; Alfanaar, Rokiy; Maryanti, Evi; Iqbal, Rendy Muhamad (Vietnam Journal of Science and Technology, 2024)
Lithium-ion batteries (Li-ion batteries or LIBs) have garnered significant interest as a promising technology in the energy industry and electronic devices for the past few decades owing to their superior energy and power density profiles, small size, long cycle life, low self-discharge rate, no memory effect, long-lasting power properties, and environmental friendly. The ongoing advancement of electrode and electrolyte materials has contributed significantly to enhancing and spreading the application of lithium-ion battery technology. Among the non-precious metal-based materials, perovskites have emerged as attention over the last decade, holding a prominent position in materials and energy. Due to their unique physical and chemical properties, these materials have garnered particular interest for their potential application in electrochemical energy devices. Perovskite oxides have piqued the interest of researchers as potential catalysts in Li-O₂ batteries due to their remarkable electrochemical stability, high electronic and ionic conductivity, and the ability to modify their properties through doping and element substitution. The purpose of this article is to provide an overview of recent developments in the application of perovskites as lithium-ion battery materials, including the exploration of novel compositions and structures, optimization of fabrication methods, and a deeper understanding of the fundamental mechanisms that can unveil the potential of perovskite materials.